Female unemployment, mobile money innovations and doing business by females - Simplice Asongu; Nicholas M. Odhiambo (Journal of Innovation and Entrepreneurship, 2023)
The purpose of this study is to complement extant literature by examining how mobile money innovations can moderate the unfavorable incidence of female unemployment on female doing of business in 44 countries from sub-Saharan Africa for the period 2004 to 2018. The empirical evidence is based on interactive quantile regressions. The employed doing business constraints are the procedures a woman has to go through to start a business and the time for women to set up a business, while the engaged mobile money innovations are: (i) registered mobile money agents (registered mobile money agents per 1000 km2 and registered mobile money agents per 100,000 adults) and (ii) active mobile money agents (active mobile money agents per 1000 km2 and active mobile money agents per 100,000 adults). The hypothesis that mobile money innovation moderates the unfavorable incidence of female unemployment on business constraints is overwhelmingly invalid. The invalidity of the tested hypothesis is clarified, and the policy implications are discussed.
Keywords: G20; I10; I20; I32; O40; 650; Doing business; Financial inclusion; Mobile phones; Sub-Saharan Africa; Women